PENGARUH MEDIA ASSEMBLR EDU BERBASIS AUGMENTED REALITY TERHADAP HASIL BELAJAR SISWA PADA PEMBELAJARAN IPAS KELAS IV SD NEGERI 104205 TEMBUNG - Maria Ekaristina Siregar; Laurensia Masri Perangin-angin (STKIP Subang, 2026)
This study aimed to determine the effect of Assemblr Edu media based on Augmented Reality on students' learning outcomes in the IPAS learning, specifically on the topic of states of matter and their changes, in grade IV at SD Negeri 104205 Tembung. This study employed a quantitative approach using a Quasi-Experimental Design with a Pretest-Posttest Control Group Design. The sample consisted of two classes: an experimental class that received instruction using Assemblr Edu media based on Augmented Reality and a control class that received instruction using YouTube video media. Data were collected through learning outcome tests in the form of pretests and posttests. The data were analyzed using normality tests, homogeneity tests, and hypothesis testing through the t-test. This study was motivated by the low learning outcomes of students in IPAS learning, indicating the need for instructional media that can help students understand concepts more concretely and attractively. The results showed that the average posttest score of the experimental class was 80, while the average posttest score of the control class was 67,78. The hypothesis testing revealed that the calculated t-value was 3,8643 and the t-table value was 2,0322 at a significance level of 0,05. Since t-count was greater than t-table, Ha was accepted and H0 was rejected. Therefore, it can be concluded that Assemblr Edu media based on Augmented Reality had a significant effect on students' learning outcomes in IPAS learning on the topic of states of matter and their changes in grade IV at SD Negeri 104205 Tembung.